School of Education : center of excellence project. - Centro Escolar University (Manila : Centro Escolar University, 2013)
This module on CB-PAST does not stand alone. It is an interconnected system within a bigger system education that needs to be neatly woven to get good results.
Module 1. CB-PAST Tools for individual personal and professional development of teachers -- Module 2. Learner-centered principles and practices -- Module 3. Facilitating Active learning -- Module 4. Establishing school-family-community Linkages -- Module 5. Global Education and the global teacher -- Module 6. Continuing Professional Education for teachers.
CEU-COE NCBTS-based in-service teacher training modules.
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES